DIFFICULTIES FACING NOVICE TEACHER-RESEARCHERS IN TERMS OF WORKING CONDITIONS AND THE SUPPORT THEY NEED - Lan, Le Thuy (VNU Journal of Foreign Studies; Vol 38 No 3DO - 10.25073/2525-2445/vnufs.4842, 2022)
The present study explores the difficulties that novice lecturers at one faculty in a university in Hanoi might face in conducting research as part of their job, especially those related to working conditions and further support they might need in this practice. The study used qualitative method of interview with six novice teachers. The outcomes show that the working conditions received mixed responses, with positive ones towards the availability of facilities/resources, information about research opportunities and negative ones towards research pressure, lack of time and lack of mentoring from experienced colleagues. Further support was then called for in the form of more financial aids and personal mentoring as well as reconsideration in research requirements on novice teachers by the school.